2015
DOI: 10.1007/s00256-015-2183-8
|View full text |Cite
|
Sign up to set email alerts
|

Irreducible superolateral dislocation of the glenohumeral joint

Abstract: The overwhelming majority of glenohumeral dislocations are anterior dislocations that either spontaneously reduce or are reduced at the point of care without significant complications. Posterior dislocations are uncommon, and superior and inferior dislocations are even rarer. We present a case of "superolateral" shoulder dislocation in which the entire rotator cuff was torn either off its insertion or at the musculotendinous junction in combination with a large longitudinal split tear of the deltoid muscle. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…After review, 12 articles fit our inclusion criteria ( Figure 1 ). 5 10 , 15 , 18 , 22 , 24 , 25 , 30 All studies were single case reports (level 4 evidence).…”
Section: Resultsmentioning
confidence: 99%
“…After review, 12 articles fit our inclusion criteria ( Figure 1 ). 5 10 , 15 , 18 , 22 , 24 , 25 , 30 All studies were single case reports (level 4 evidence).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that anterosuperior shoulder dislocation, in which dislocation occurs in the direction anterior to the acromion, is caused by a combination of rotator cuff insufficiency including the supraspinatus and subscapularis tendons, a loss of the coracoacromial arch, and a rupture of deltoid anterior fibers [4, 5]. In addition, it has been reported that superolateral dislocation, in which dislocation occurs in the direction of the lateral side of the acromion, is caused by a longitudinal split tear of the anterolateral deltoid muscle and a massive rotator cuff tear [7]. However, dislocation in the direction of the posterior acromion, namely posterosuperior dislocation, was observed for the first time in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical options for superior shoulder dislocations include rotator cuff repair or reverse shoulder arthroplasty, in addition to deltoid repair. While there is a report stating that open reduction and rotator cuff repair achieved reduction in a young patient with superolateral dislocation [7], another report states that early re-dislocation was observed in an elderly patient with Parkinson’s disease suffering from anterosuperior dislocation, and a rotator cuff repair was performed [5]. Therefore, the outcome of rotator cuff repair for superior shoulder dislocation remains controversial and further research and investigation is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interposition of the LHBT alone or in combination with greater tuberosity fracture was the most common obstacle to reduction [5, 7, 9, 11-16], followed by subscapularis tendon interposition either tightened around the humeral head or as soft tissue hindrance inside glenoid [17, 19-24]. Other reasons for an unsuccessful closed reduction were the interference of bony fragments [18, 25] or the labrum [7] inside glenoid, the presence of a “shield” fracture of both tuberosities [15], interposition of the musculocutaneus nerve [26] and two cases of anterosuperior dislocation with torn rotator cuff and the humeral head lying underneath deltoid muscle [8, 10]. …”
Section: Discussionmentioning
confidence: 99%